2020
DOI: 10.1002/eji.202048616
|View full text |Cite
|
Sign up to set email alerts
|

Functionally distinct IFN‐γ+IL‐17A+ Th cells in experimental autoimmune uveitis: T‐cell heterogeneity, migration, and steroid response

Abstract: Immunopathogenic roles for both Th1 (CD4 + IFN-γ +) and Th17 (CD4 + IL-17A +) cells have been demonstrated in experimental autoimmune uveitis (EAU). However, the role for Th17/Th1 (CD4 + T cells co-expressing IFN-γ and IL-17A) cells in EAU is not yet understood. Using interphotoreceptor retinoid-binding protein peptide-induced EAU in mice, we found increased levels of Th17/Th1 cells in EAU retinae (mean 9.6 ± 4.2%) and draining LNs (mean 8.4 ± 3.9%; p = 0.01) relative to controls. Topical dexamethasone treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Interleukin 17 (IL-17) producing Th17 cells and IFN-gproducing Th1 cells, have been thought to be important in the immunopathogenesis of uveitis and EAU (8,13). The IFN-g + IL-17A + phenotype, named Th1/Th17 subset, is associated with Th17-mediated diseases in human and animal models (14). And it has been recently shown that CD4 + T cells or Th17 cells have substantial plasticity and display important functions in the tissue microenvironment during chronic inflammation (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin 17 (IL-17) producing Th17 cells and IFN-gproducing Th1 cells, have been thought to be important in the immunopathogenesis of uveitis and EAU (8,13). The IFN-g + IL-17A + phenotype, named Th1/Th17 subset, is associated with Th17-mediated diseases in human and animal models (14). And it has been recently shown that CD4 + T cells or Th17 cells have substantial plasticity and display important functions in the tissue microenvironment during chronic inflammation (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Th17 cells have substantial plasticity and readily acquire ability to produce IFNγ in addition to IL-17 [15,38]. Our previous data suggested that the ability of Th17/Th1 cells to produce both IL-17 and IFNγ correlates with RORγt + and Tbet + transcription factor co-expression [36]. This subset, so-called Th17/Th1 cells, is thought to be due to Th17 cell plasticity, facilitated through IL-12 or IL-23 stimulation [39,40].…”
Section: Role Of Th17/th1 Cells In Eaumentioning
confidence: 88%
“…Human Th17/Th1 (IL-17 + IFNγ + ) cells are characterized by their expression of CD161, CCR6, IL-17 receptor E, RORC, and IL-4-induced gene 1 [38,42,43]. These Th17/Th1 cells are characterized by their resistance to corticosteroids in IRBP-induced EAU at peak disease, which may be due to a stable expression of multi-drug transporter type 1 (MDR1), an ATP-dependent membrane efflux pump [36]. It is supposed that Th17/Th1 cells lose their ability to produce IL-17 and become non-classical Th1 cells (expressing both RORγt and Tbet, but producing only IFNγ) following an IL-17/IFNγ double-producing phase [44].…”
Section: Role Of Th17/th1 Cells In Eaumentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, we are the first to describe these differences in a direct comparison between PBMC and CD4 sorted subpopulations. Since CD4 + T cells are the major players in HAU, ERU and the induced uveitis models (1,42,43), we subsequently focused on the metabolic phenotype of this specific cell subset. We could demonstrate that CD4 + T cells of ERU cases utilized the oxidative phosphorylation pathway in basal state to a significantly higher amount than control cells (Figure 1A).…”
Section: Discussionmentioning
confidence: 99%